A ditadura brasileira sob o olhar juvenil: uma análise dos filmes Nunca fomos tão felizes e O ano em que meus pais saíram de férias - Souza, Roberta Lemos de (2016)
The purpose of this study is to analyze two films – We’ve Never Been So Happy (Murilo Salles, 1984) and The Year My Parents Went on Vacation (Cao Hamburger, 2006) – that reveal a youthful perspective on the military dictatorship in Brazil (1964-1985). The major objective of this study is to investigate in which ways both films help build memories, by analyzing their narratives as well as the historical context in which they were produced